The Slaveholders' Dilemma : Freedom and Progress in Southern Conservative Thought, 1820-1860 - Genovese, Eugene D., 1930-2012 (The University of South Carolina Press, 2021)
A new foreword is provided by Douglas Ambrose, professor of history at Hamilton College and author of Henry Hughes and Proslavery Thought in the Old South.